UPAYA MENINGKATKAN KETERAMPILAN BERHITUNG SISWA KELAS I SD MELALUI MEDIA KARTU HITUNG DI SD NEGERI 03 NANGA NGERI TAHUN 2024/2025 - Asriyati, Novi; wibowo, dwi cahyadi; Rismawati, Melinda; Putri, Anike (STKIP Persada Khatulistiwa Sintang, 2025)
media in first-grade students at SD Negeri 03 Nanga Ngeri. This research employed Classroom Action Research (CAR) as its method. The subjects were 13 first-grade students. Data collection techniques included observation sheets, interviews, test questions, and documentation. Data analysis followed stages of data collection, data reduction, data display, and conclusion drawing. The results indicate that: (1) the learning process using counting cards ran effectively, as evidenced by teacher activity scores increasing from 81.25 (good) in cycle I to 93.75 (very good) in cycle II; (2) students’ counting skills improved significantly, with the average score rising from 50.76 in cycle I (38.46% classical completeness) to 80.76 in cycle II (84.61% classical completeness); (3) students’ responses were very positive, showing enthusiasm and enjoyment in using counting cards. It can be concluded that the use of counting card media effectively enhances the counting skills of first-grade elementary school students.